Kepentingan Australia Dalam Pembuatan Kebijakan Kemasan Polos Produk Rokok (Tobacco Plain Packaging) Tahun 2012 - Emi Mahadewi, Gusti Ayu Kadek (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This research aims to describe the Australia’s interest in making plain packaging policy for cigarette products (Tobacco Plain Packaging) in 2012. Smokers in Australia is quite high, consisting of both men, women and teenagers and adults. Cigarette are legally accessible in Australia. But, since 2012 Australia has began to implement regulation about packaging for every cigarette product marketed in Australia. This study used qualitative research method with secondary data collection and that focuses on state level analysis. As for framework of thinking in this study uses the concept health security as national interest. The result of this research show that Australia in making plain packaging policy for cigarette products for the interest of public health in Australia. Keywords : Plain packaging policy, tobacco packaging, health security, national interest.